Readers’ Responses to Homoerotism on Indonesian Online Fictions - Andriadi Andriadi (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2022)
The dominant masculine stereotype constructed in our society's view is considered to be restrictive and unfavorable in some aspects inherent in masculine gender. This condition sometimes makes men depressed and suffer because they cannot express certain feelings and emotions which also require other men's point of view and internalize certain values. Bromance is considered as a concept against masculine views that develop in society so that they are able to express their feelings, empathize with each other, motivate each other, and together show concern in difficult times so that they can share the problems they face and find solutions from a male point of view. man. This study aims to explore he  reader’ respond to homoeroticism depicted in Indonesian online fiction  and an offer  to  ideal homosocial concept as a solution for male friendship that should be depicted in a fictional world as the basis for building a better civilization and source of literacy. This study uses a qualitative method. The result showed that the male body becomes the source of the emergence of homoeroticism in friendship interraction. Sexual stimulation and words that have homoerotic tendencies in character interactions lead to sexual feelings. Strong and intense emotions lead them to feelings of homoeroticism. The more intimate emotional and physical closeness leads them to change their sexual desire towards other sexual acts. The offer of the concept of the ideal friendship of heterosexual men in a fictional world should include aspects: togetherness, sharing problems openly and comfortably, providing emotional support, and giving surprises by avoiding things that are not accepted by our society, namely affection without deep emotions. and a description of ethical interactions without physical contact so that the strength of male homosocial bonds is built as well as to uphold certain images of masculinity and sexuality in accordance with the masculine stereotypes adopted and developed in the society. In other words, men must maintain ethics and dignity in a friendship